Funcionalidad familiar y autoestima y su relación con el rendimiento académico en adolescentes - 2016 - Azañero Romero, Geanmarco (2017)
The research aimed to determine the relationship between personal factors: family functionality and level of self-esteem with academic performance in adolescents of the Educational Institution "José Andrés Razuri" - 2016. The sample was made up of 210 adolescents from third And fourth year of high school. The obtained information was processed and analyzed by: the statistical test of independence of criteria "Chi square" for related samples; The results are presented in simple and double-entry tables. We used the Family Functionality Questionnaire and Coopersmith's Self-Esteem Inventory. The results found lead to the following conclusions: With regard to the family functionality, it was found that 58.1% presented good functionality, a significant percentage 36.7% presented family dysfunction, and 5.2% presented severe dysfunctionality. Regarding the self-esteem variable, 54.8% had high self-esteem, 41.4% had average self-esteem, and 3.8% had low self-esteem. Academic performance, 7.6% had excellent academic performance, 39.5% had a good academic performance, 51.4% had an acceptable performance and 1.5% showed poor performance. Regarding the relation between family functionality and academic performance, a weak but significant association was found (X2 = 0.244, P = 0.038). The relationship between self-esteem and academic performance was found to be a mean but significant association (X2 = 0.405, P = 0.000).